DEVELOPING OF HADANG TRADITIONAL GAME THROUGH PLYOMETRIC TRAINING ON FIFTH GRADE STUDENTS OF SD NEGERI 98 NORTH BENGKULU - Supriyanto Supriyanto; Martiani Martiani (Universitas Negeri Medan, 2019)
Fighting games are regional games from Indonesia that we can now meet and play with children. This game is a team game consisting of two teams, each team consists of 5-7 people. The core of the game is to confront the opponent so that he can't get past the line with the rules that have been determined. To win a player must collect points by passing the guards from the row to the last row, and vice versa. This study aims to determine the results of the development of the method of plyometric training (Scissor Jump, Stride Jump Crossover, Lateral Bound) and for playing games. Plyometric is a method of training that focuses on movement at high speed. The method used in this study is research-based development (R & D), aimed at developing plyometric training products. The research sample is the fifth grade students of SD North 98 North Bengkulu, amounting to 28 people. In the initial observation researchers have obtained data in the form of pre-tests and the results of interviews from both teachers and students. Based on the results of the study using the plyometric method shows that the basic physical condition of the fifth grade students of North Bengkulu Elementary School 98 in the good category. This is evidenced by the results of cognitive and psychomotor tests that have been conducted on small group trials with the acquisition of a percentage of 20% (2 people) with very good categories, 50% percentage (5 people) with good categories, 10% percentage (1 person) with enough categories and a percentage of 20% (2 people) with less categories. Whereas in large group trials there was a percentage of 21% (6 people) with a very good category, a percentage of 43% (12 people) with a good category, a percentage of 25% (7 people) with enough categories, and a percentage of 11% (3 people) with less category. Thus, it can be concluded that the plyometric method is feasible to be used for fifth grade students of North Bengkulu Elementary School 98. Suggestions to teachers assess that the use of the plyometric method is an alternative in the learning process, especially traditional games.